e-BINTECH 5.0: Desa Siaga COVID-19 Berbasis Edubioneurolitechnopreneurship Menuju Indonesia 5.0 - Dito Anurogo; Agusdiwana Suarni; Arli Parikesit; Muchlis Sofro; Wahyu Aristyaning Putri (STMIK Royal, 2021)
Abstract: The e-Bintech 5.0 online workshop was held to sharpen the concept of village 5.0 that is a multidisciplinary acculturation-constellation. In this workshop, multiplatform frameworks were successfully formulated as a basic guideline for village developments towards the glory of Indonesia. Pentahelix platform synergy is needed (academics, business, government, community, media) supported by relevant stakeholders for fostering a futuristic village towards the creation of Indonesia 5.0, especially in terms of ease of investment, simplification of bureaucracy and administration.Key Words: edubioneurolitechnopreneurship; Indonesia 5.0; pentahelix; village 5.0 Abstrak: Lokakarya daring e-Bintech 5.0 diadakan untuk menajamkan konsep desa 5.0 yang merupakan akulturasi-konstelasi multidisipliner. Dalam lokakarya ini, berhasil dirumuskan multiplatform-frameworks sebagai pedoman dasar pengembangan-pembangunan desa menuju kejayaan Indonesia. Diperlukan sinergi platform pentahelix (akademisi, bisnis, pemerintah, komunitas, media) didukung stakeholders terkait untuk pembinaan desa futuristik menuju terciptanya Indonesia 5.0, terutama dalam hal kemudahan investasi, simplifikasi birokrasi dan administrasi.